Pengaruh Delay Cord Clamping Terhadap Kadar Hemoglobin Bayi Baru Lahir Di PMB Diah Rosita Kabupaten Bogor Tahun 2022: The Effect of Delay Cord Clamping on Hemoglobin Levels of New Born Babies in PMB Diah Rosita, Bogor Regency in 2022 - Ginting, Triyana (Dohara POAJ, 2023)
Introduction: Delay Cord Clamping can increase iron storage at birth so as to prevent iron deficiency anemia and can provide an additional 80-100 ml of blood in newborns. The purpose of this study was to determine the effect of Delay Cord Clamping on the hemoglobin level of newborns in PMB Diah Rosita, Bogor Regency in 2022 Methods: This research is quantitative research. The design used is a quasi-experimental research design with Posttest Only Control Design Group Design Results: The results of this study are newborn hemoglobin levels in the intervention group averaged 18,320 and newborn hemoglobin levels in the control group averaged 15,500; statistical tests using Independent T-Test obtained a value of p = 0,000 < 0,05 which means Ho is rejected and Ha is accepted so that there is an effect of Delay Cord Clamping on newborn hemoglobin levels Discussion: This can have a positive impact on newborns which is expected to be an alternative to prevent iron deficiency anemia in newborns.